COMBINED STRATEGIES TO ACHIEVE ROBUST STRUCTURES - Tanner, Peter; ICASP14; Hingorani, Ramon (My University, 2023)
While the practical importance of designing and building robust structures is well recognized, the relevant code rules currently in place are often vague or confusing. Cross-referencing, in turn, may lead to loops around rules that, confounding engineers, are counterproductive. A major issue in this regard is the lack of a general design philosophy for robustness, a consequence of the complexity of the problem itself, since any solution intended to improve system performance for some scenarios may degrade it for others. Building on that premise, a practical approach to design robust structures has been proposed in previous papers, applying a combination of strategies to meet all structural performance requirements, including robustness, as economically as possible. The proposal generally envisages the conceptual design of continuous, ductile structural systems due to their inherent advantages for identified design situations, such as redistribution capacity for internal forces and energy dissipation. In order to avoid progressive collapse given the occurrence of local failure due to unidentified accidental situations, either alternative load paths or predefined collapse mechanisms should be built into such systems. The proposal includes a procedure to achieve correspondence between assumed and real mechanisms in case of failure of any member on which the strength and stability of the system or subsystem depends, the so-called key members. For the design or assessment of such key members, risk-based target reliability indices have been developed for both, persistent and accidental situations. In terms of the remaining structural system left standing after key member failure, both the relevant design situations and the performance requirements depend on the design goal, e.g., rescuing any endangered people. This practical approach to designing structures for robustness is summarized in the paper. In addition, considerations are made about the target reliability for the remaining system, taking into account that in robust design the possible failure of a key member is due to an unidentified accidental situation. Finally, the approach, which combines different robustness strategies and includes risk-based considerations, is illustrated with a case study.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED